2014
DOI: 10.28945/2050
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Pursuing an Engineering PhD and Perceptions of its Added Value: A U.S.-based Study

Abstract: Engineering doctor of philosophy (PhD) holders possess expertise that is vital to addressing society's grand challenges, but the dismal number of U.S. citizens pursuing the degree suggests many are not convinced of its value. There are few studies that have explored what motivates people in other disciplines to pursue a PhD, and not many of these were in the context of engineering. In this study, forty engineering PhD holders working in academia and industry in the U.S. described their motivations for earning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…She said, "I want to get a regular item in our university, so I decided to pursue my masters here in VSU. In our school, we cannot get a regular item if we don't have an MS [ These results are similar to the findings of some researchers showing that academic improvement and professional development or career advancement are among the graduate students' prevailing reasons for pursuing graduate education (Incikabi, Pektas, Ozgelen & Kurnaz 2013;Almeda 2014;London et al 2014). Table 3.…”
Section: Reasons For Pursuing Graduate Educationsupporting
confidence: 81%
“…She said, "I want to get a regular item in our university, so I decided to pursue my masters here in VSU. In our school, we cannot get a regular item if we don't have an MS [ These results are similar to the findings of some researchers showing that academic improvement and professional development or career advancement are among the graduate students' prevailing reasons for pursuing graduate education (Incikabi, Pektas, Ozgelen & Kurnaz 2013;Almeda 2014;London et al 2014). Table 3.…”
Section: Reasons For Pursuing Graduate Educationsupporting
confidence: 81%
“…And, as we previously noted, Gardner's (2009a) study of faculty perceptions of graduate student success also identified motivation as an essential ingredient. More recently, London et al (2014) identified reasons doctoral degree holders gave for pursing their advanced degree. However, by and large, it is notable that one of the seemingly most critical component to graduate student success -student motivation -appears to receive the least amount of attention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to demographic characteristics, graduate student attrition/retention literature has highlighted a host of other internal and external student factors, such as motivation, knowledge and skills, and financial resources (Bain, Fedynich, & Knight, 2011;Hirschberg & Itkin;1978;London, Cox, Ahn, Branch, & Zephirin, 2014;Spaulding & Rockinson-Szapkiw, 2012). In regard to motivation, for example, Ponton, Derrick, and Carr (2004) asserted in response to a Chronicle of Higher Education discussion of doctoral attrition, "Doctor Dropout" (Smallwood, 2004), "… the presence of attributes that are important for successful doctoral matriculation [are] desire, resourcefulness, initiative, and persistence" (p. B4).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…As demonstrated by Jones (2013), most extant literature has not been centered on doctoral student motivation. Still, there is a growing body of literature examining doctoral students' initial motivation in academic disciplines such as engineering (Baytiyeh & Naja, 2011;Guerin & Ranasinghe, 2010;London, Cox, Ahn, Branch, & Zephirin, 2014;Mokhtar, 2012;Peters & Daly, 2013), education (Jablonski, 2001Leonard, Becker, & Coate, 2005;Stehlik, 2011;Wellington & Sikes, 2006), and business (Stiber, 2000). Some studies were conducted using online surveys with motivational factors selected a priori by the researcher based on existing literature (Anderson & Swazey, 1998;Stehlik, 2011;Stiber, 2000).…”
Section: Doctoral Student Motivationmentioning
confidence: 99%